Coligand modifications fine-tuned the structure and magnetic properties of two triple-bridged azido-Cu(ii) chain compounds exhibiting ferromagnetic ordering and slow relaxation. Issue 4 (5th January 2017) - Liu, Xiangyu; Li, Feifei; Ma, Xiaohui; Cen, Peipei; Luo, Shuchang; Shi, Quan; Ma, Shenru; Wu, Yuewei; Zhang, Chengcheng; Xu, Zhao; Song, Weiming; Xie, Gang; et al.
Abstract : Two triple-bridged azido-Cu(ii ) compounds with different benzoates as coligands exhibit distinct magnetic properties. Abstract : Employing two benzoate derivatives with different numbers of non-coordinated fluoro-substituents, 2-fluorobenzoic acid (2-Hfba) and 2, 6-difluorobenzoic acid (2, 6-Hdfba), two new azido-copper coordination polymers, [Cu(2-fba)(N3 )(CH3 OH)] n (1 ) and [Cu(2, 6-dfba)(N3 )(CH3 OH)] n (2 ), have been successfully isolated, and then structurally and magnetically investigated. Single crystal structure analysis demonstrates that the metal cations in the two resulting compounds are connected by the alternating triple-bridge of μ-1, 1-azido, syn, syn -carboxylate and μ2-methanol, contributing to analogously linear 1D Cu(ii ) chain-like motifs with slightly different intrachain and interchain geometric parameters. The fine-tuned structures lead to variant magnetic properties in the two title compounds. Although a dominant ferromagnetic coupling between adjacent Cu(ii ) ions within each chain due to the counter-complementarity of the multiple superexchange pathways is observed in both compounds, the interesting plots of magnetic ordering and slow magnetic relaxation, which are rare in most of the reported azido-Cu(ii ) architectures, only occur in compound1, while2 behaves as an antiferromagnet consisting of ferromagnetic Cu(ii ) chains. The heat-capacity experiments further emphasize the characteristic long-range ferromagnetic ordering in1 and the typical behavior of antiferromagnets in2 . Moreover, density functional theory (DFT) calculations (using different methods and basis sets) have been performed on both compounds to obtain the qualitatively theoretical interpretation of the magnetic behaviors.